Convergent adaptation to dangerous prey proceeds through the same first‐step mutation in the garter snake Thamnophis sirtalis1. (21st April 2017) - Hague, Michael T.J.; Feldman, Chris R.; Brodie, Edmund D.; Brodie, Edmund D.
Abstract : Convergent phenotypes often result from similar underlying genetics, but recent work suggests convergence may also occur in the historical order of substitutions en route to an adaptive outcome. We characterized convergence in the mutational steps to two independent outcomes of tetrodotoxin (TTX) resistance in separate geographic lineages of the common garter snake ( Thamnophis sirtalis ) that coevolved with toxic newts. Resistance is largely conferred by amino acid changes in the skeletal muscle sodium channel (NaV 1.4) that interfere with TTX‐binding. We sampled variation in NaV 1.4 throughout western North America and found clear evidence that TTX‐resistant changes in both lineages began with the same isoleucine‐valine mutation (I1561V) within the outer pore of NaV 1.4. Other point mutations in the pore, shown to confer much greater resistance, accumulate later in the evolutionary progression and always occur together with the initial I1561V change. A gene tree of NaV 1.4 suggests the I1561V mutations in each lineage are not identical‐by‐decent, but rather they arose independently. Convergence in the evolution of channel resistance is likely the result of shared biases in the two lineages of T. sirtalis —only a few mutational routes can confer TTX resistance while maintaining the conserved function of voltage‐gated sodium channels.